Sex-related differences in treatment and outcome of chronic limb-threatening ischaemia: a real-world cohort. (3rd February 2022) - Makowski, Lena; Köppe, Jeanette; Engelbertz, Christiane; Kühnemund, Leonie; Fischer, Alicia J; Lange, Stefan A; Dröge, Patrik; Ruhnke, Thomas; Günster, Christian; Malyar, Nasser; Gerß, Joachim; Freisinger, Eva; et al.
Abstract: Aims: The prevalence of chronic limb-threatening ischaemia (CLTI) is increasing and available data often derive from cohorts with various selection criteria. In the present study, we included CLTI patients and studied sex-related differences in their risk profile, vascular procedures, and long-term outcome. Methods and results: We analysed 199 953 unselected patients of the largest public health insurance in Germany (AOK: Local healthcare funds), hospitalized between 2010 and 2017 for a main diagnosis of CLTI. A baseline period of 2 years before index hospitalization to assess comorbidities and previous procedures, and a follow-up period until 2018 were included. Female CLTI patients were older (median 81.4 vs. 73.8 years in males; P  < 0.001) and more often diagnosed with hypertension, atrial fibrillation, chronic heart failure, and chronic kidney disease. Male patients suffered more frequently from diabetes mellitus, dyslipidaemia, smoking, cerebrovascular disease, and chronic coronary syndrome (all P  < 0.001). Within hospitalized CLTI patients, females represent the minority (43% vs. 57%; P  < 0.001) and during index hospitalization, women underwent less frequently diagnostic angiographies (67 vs. 70%) and revascularization procedures (61 vs. 65%; both P  < 0.001). Moreover, women received less frequently guideline-recommended drugs like statins (35 vs. 43%) and antithrombotic therapy (48 vs. 53%; both P  < 0.001) at baseline. Interestingly, after including age and comorbidities in a Cox regression analysis, female sex was associated with increased overall-survival (OS) [hazard ratio (HR) 0.95; 95% confidence interval (CI) 0.94–0.96] and amputation-free survival (AFS) (HR 0.84; 95% CI 0.83–0.85; both P  < 0.001). Conclusion: Female patients with CLTI were older, underwent less often vascular procedures, and received less frequently guideline-recommended medication. Nevertheless, female sex was independently associated with better OS and AFS during follow-up. Structured Graphical Abstract: An analysis of 199 953 unselected CLTI patients of the largest public health insurance in Germany (AOK) showed that female CLTI patients were older and display the minority of the hospitalized CLTI patients. During index hospitalization and during follow-up period, women underwent less frequently any vascular procedure (diagnostic angiography or revascularization procedures) and, moreover, received less frequently guideline-recommended drugs like statins or antithrombotic therapy. Interestingly, after including age and comorbidities in a Cox regression analysis, female sex was associated with increased OS and AFS.